2019
DOI: 10.3390/ijms20205226
|View full text |Cite
|
Sign up to set email alerts
|

The ST2/Interleukin-33 Axis in Hematologic Malignancies: The IL-33 Paradox

Abstract: Interleukin (IL)-33 is a chromatin-related nuclear interleukin that is a component of IL-1 family. IL-33 production augments the course of inflammation after cell damage or death. It is discharged into the extracellular space. IL-33 is regarded as an “alarmin” able to stimulate several effectors of the immune system, regulating numerous immune responses comprising cancer immune reactions. IL-33 has been demonstrated to influence tumorigenesis. However, as far as this cytokine is concerned, we are faced with wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 109 publications
0
8
0
Order By: Relevance
“…IL-33 reinforces the TNF-alpha induced secretion of IL-6, VEGF, and MCP-1. However, data on IL-33 serum levels in Pso are controversial ( 113 ). A large number of studies suggest that a localized, rather than a generalized, IL-33 linked inflammatory pattern is evident in Pso ( 114 ).…”
Section: The Role Of Il-33mentioning
confidence: 99%
See 2 more Smart Citations
“…IL-33 reinforces the TNF-alpha induced secretion of IL-6, VEGF, and MCP-1. However, data on IL-33 serum levels in Pso are controversial ( 113 ). A large number of studies suggest that a localized, rather than a generalized, IL-33 linked inflammatory pattern is evident in Pso ( 114 ).…”
Section: The Role Of Il-33mentioning
confidence: 99%
“…The MAPK-activated protein kinases MK2 and MK3, function as sensors of cell injury and exert pivotal roles in IL-33-induced cytokine production by mast cells in inflammatory responses ( 87 , 98 , 107 ). Due to its pleiotropic nature, IL-33 exerts contrasting roles in different diseases ( 87 , 88 ), i.e., IL-33 can either drive the underlying inflammation or promote its resolution ( 99 , 113 ) according to the individual inflammatory context. Disease severity and changes in relation to hormonal influences contribute to the bone remodeling effects of IL-33.…”
Section: The Role Of Il-33mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, IL-33 as well as ST2 have been implicated in enhanced pathology and progression of colorectal, lung, breast and gastric cancer, as well as melanoma, head and neck squamous cell carcinoma and cholangiocarcinoma (Gorbacheva and Mitkin, 2019;Hong et al, 2019). In terms of hematological malignancies, the effects of IL-33 are controversial as a negative role has been identified for Chronic myelogenous leukemia (CML), while a positive role was shown for Acute myeloid leukemia (AML) (Allegra et al, 2019). A very recent paper by Yue et al showed that IL-33 stimulates the recruitment of Tregs through the NF-kB/CCL2 pathway, thereby enhancing tumor growth and metastasis in esophageal squamous cell carcinoma (Yue et al, 2019).…”
Section: Role Of Il-33 Referencesmentioning
confidence: 99%
“…However, in the context of cancer, IL-33 aids in tumor immune evasion by upregulating the activity, survival and expansion of myeloid derived suppressor cells via ST2 signaling, which was reduced in ST2 −/− mice (Xiao et al, 2016). Recent discoveries have further suggested that IL-33 can induce the proliferation, survival, and metastasis of cancer cells (Allegra et al, 2019;Gorbacheva and Mitkin, 2019). IL-33 is also known to exacerbate asthmatic and allergic inflammation in the skin, GI tract and lungs through the ST2-mediated activation of basophils, eosinophils, mast cells, dendritic cells, macrophages and ILC2s by promoting the chemo-attraction of Th2 cells and the production of Th2-associated cytokines by various cell types (Louten et al, 2011;Bartemes et al, 2012;Sjoberg et al, 2017;Chan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%